Polymer-gold nanohybrids with potential use in bimodal MRI/CT: Enhancing the relaxometric properties of Gd(III) complexes - Beija, M.; Li, Y.; Duong, H.; Laurent, S.; Elst, L.; Muller, R.; Lowe, Andrew; Davis, T.; Boyer, C. (2012)
We present a new synthetic strategy to produce Gd(III)-decorated gold nanoparticles (AuNPs) for potential use as bimodal contrast agents (CA) for computed X-ray tomography (CT) and magnetic resonance imaging (MRI). The hybrid AuNPs exhibit high molar relaxivities (>12 000 mM−1 s−1 per particle), indicative of highly efficient CT/MRI CAs.